Overproduction of protein-bound polysaccharides from a Coriolus versicolor strain by submerged fermentation - Arteiro, José (2012)
Some mushroom strains are able to synthesize polysaccharopeptides with antitumoral and immunostimulating properties. The aim of this study was to define experimental conditions to optimize the production of protein-bound polysaccharides by Coriolus versicolor. In order to evaluate and to optimize the production of these compounds, submerse cultures were performed with four different carbon sources: glucose, maltose, sucrose and mannitol. Additionally, aiming for a clean process and to reduce the medium cost, two kinds of agroindustrial residues were used: tomato pomace and beet wastes. The highest polysaccharide concentration was achieved with tomato pomace as agroindustrial residue corresponding to the 14th day of culture. Based on these results C. versicolor was cultivated in a basal medium plus tomato pomace in a stirred bioreactor. Endocellular and exocellular protein-bound polysaccharides were quantified. The concentration of the polysaccharide compounds was higher in the supernatant than in mycelia and supernatant complex has higher protein content. The main protein-bound polysaccharides produced by C. versicolor ranged between molecular weights of 1.3x103- 8.9x104 Da. The comparison of the results obtained in this study with those reported in the literature, let us to confirm the interest of this selected culture medium with tomato pomace, in order to maximise the production of complexes protein-polysaccharides by C. versicolor. Besides, this clean process allows valuing the agro-industrial residues with a low cost and a higher production of polysaccharide compounds.